(untitled) (International Journal of Engineering and Computer Science, 2015)
This project aims to gift an application that’s ready of communication the standard mouse with the external body part as brand new thanks to act with the pc. Countenance (nose tip and eyes) are detected and half tracked in time period to use their actions as mouse events. In our work we tend to compensate people that have hands disabilities that stop them from victimization the mouse by planning an application that uses countenance (nose tip and eyes) to act with the pc. It will be applied to a large vary of face scales our basic strategy for detection is quick extraction of face candidate with a Six-Segmented Rectangular (SSR) filter and face verification by a support vector machine (SVM). A motion cue is employed in a very easy thanks to avoid learning false candidates within the background. In face trailing the patter ns of between-the eyes(BTE) are half-tracked with change example matching.